Nanobiopesticides in sustainable agriculture: developments, challenges, and perspectives - Pan, Xiaohong; Guo, Xueping; Zhai, Tianyun; Zhang, Dingyang; Rao, Wenhua; Cao, Fang; Guan, Xiong (Environmental science. Nano, 2023)
Environment-friendly nanomaterials with biodegradable, responsive, and biocompatible properties have attracted considerable interest for exploring safe and efficient pesticides, and applying nanotechnology to develop new nanopesticide formulations would avoid the hazards of chemical pesticides and improve the efficacy of biopesticides. It can also be conducive to the development of less toxic biopesticides with increased stability of active ingredients, favorable biological safety, and enhanced activity on target pests. At present, there are comprehensive research papers, reviews, and books available on nanopesticides, but there are few reviews on nanobiopesticides. This review summarizes the main applications of nanotechnology in biopesticide formulation (such as nanoinsecticides, nanofungicides, nanobactericides, nanobioherbicides, and RNA pesticides), explores the possible uptake and transport mechanisms of nanobiopesticides in plants, analyzes its possible fate and impact on environment, and describes the challenges and possible risk of nanobiopesticides. Overall, this review provides a promising and comprehensive environmental perspective on the latest nanotechnology in the biopesticides field. Applications of nanotechnology in biopesticides could achieve controlled release, increase the solubility, and exhibit location targeting and strong compatibility.